RESILIENSI USAHA PENGOLAHAN IKAN KERING SKALA KECIL DI PROVINSI BENGKULU INDONESIA - Reswita; Ketut Sukiyono; Indra Cahyadinata; Satria Putra Utama (Universitas Garut, 2026)
Small-scale dried fish processing businesses play an important role in supporting the livelihoods of coastal communities and the development of the fisheries economy in Bengkulu Province. However, these businesses face various uncertainties, such as fluctuations in raw fish supply, dependence on weather conditions, and market dynamics.This study aims to measure the resilience level of dried fish processing businesses through the development of a business resilience index that integrates four main dimensions: personal resilience of business actors, anticipatory capacity, adaptive capacity, and innovative capacity. A quantitative approach was employed using a survey method of dried fish processing business actors, and the data were analyzed using the Dried Fish Processing Business Resilience Index.The results show that the resilience level of dried fish processing businesses in Bengkulu Province falls into the fairly high category. Personal resilience of business actors is the most dominant dimension, while anticipatory capacity and innovative capacity are also relatively high